Rebuilding Public Confidence in Educational Assessment - Richardson, Mary (UCL Press, 2022)
Educational assessment is important. But in the twenty-first century it is easy to feel that schooling and other phases of education are shaped entirely by certain assessments, and that assessment is only about exam results. The idea that test grades can accurately describe the aims and outcomes of education is unfair and reductive. Yet it is a pervasive and persuasive discourse. This book is about such discourses - the stories we tell each other - and how they impact public trust and confidence in educational assessment. It explains the roots and nature of assessment discourses, and proposes a restructuring of the debates in order to rebuild public confidence. It aims to challenge dominant assessment discourses and demands a more nuanced, informed debate about what happens in and beyond schools, and how this influences public thinking. Questioning the status quo needs buy-in from policymakers, teachers, parents and students, and from the broader public: from journalists, you, me, our friends and our children. Using examples from international settings to explore the nature of trust in assessment discourses, Rebuilding Public Confidence in Educational Assessment shows how these discourses can be reframed so that all aspects of the assessment system - policymaking, school planning, home practice with students - can be undertaken with confidence.